Blessing in disguise: Kenya’s prospects towards harnessing data-driven ICT techniques in quest of post-Covid-19 economic recovery - Ronoh, Lamek; Knowen, Cosmas (African Journal of Science, Technology and Social Sciences, 2022)
COVID-19 crisis caused tremendous disruptions and abrupt shut down or slow down on core business processes globally and ultimately causing a worldwide recession. The unpredicted nature of the economic informed decision data due to rapid unstructured data that was generated at a high pace, business entities were at a great risk to collapse. Kenya is no exception to these unprecedented phenomena - COVID-19 pandemic. Retrospectively, we can learn lessons from the earlier shattering worldwide pandemics such as the Spanish Flu or the great influenza which paved way to paradigm shifts in the introduction and implementation of disruptive technologies. In the recent past, there is an increasing effort on innovative technologies to make every sector sustainable to meet the opportunities arising from the COVID-19 pandemic. This paper explored and presented the latent opportunities in which Kenya’s business community in virtually all sectors/industries can harness and leverage not only for economic recovery’s sake but also creating a platform for businesses to catapult towards business reengineering maturity frameworks that is hardened with almost infinite potency of innovations. More specifically, integration of BI and AI to business processes is proposed in this paper. Leveraging BI and AI will aid business organizations transform data into useful insights that inform a businesses’ strategic and tactical decisions. Pragmatically, detailed intelligence about the status of the business using BI and machine learning techniques together with predictive analytics will be demonstrated in this paper as a panacea of economic recovery from post COVID-19 ravages when adopted and integrated well in Kenya’s business landscape. It will no doubt provide business entities with groundbreaking data-driven insights that can be leverage and be utilized to synthesize big data into a coherent action plan (using BI/AI powered economic data). This way, business entities will be able to employ this data to create post COVID-19 recovery indexes which is further used to give business entities important statistics such as predictive recovery Index that ultimately aid quick economic recovery for Kenya’s business sector by embracing the utilization of the unstructured vast data generated for the advantage of economic revolution.